A fast self-charging and temperature adaptive electrochromic energy storage device. Issue 8 (3rd February 2022) - Wang, Yue; Zhong, Xiaolan; Liu, Xueqing; Lu, Zelin; Su, Yingjie; Wang, Mengying; Diao, Xungang
Abstract : ECESDs exhibit a wide operating temperature range. They can be chemically self-charged through a spontaneous redox reaction and the energy status could be estimated by the naked eye according to the obvious color during the charge/discharge process. Abstract : Self-charging electrochromic energy storage devices have the characteristics of energy storage, energy visualization and energy self-recovery and have attracted extensive attention in recent years. However, due to the low self-charging rate and poor environmental compatibility, it is a great challenge to realize the practical application of self-charging electrochromic energy storage devices. Herein, we demonstrate a multifunctional electrochromic battery (ECESD) with rapid self-charging capability, temperature adaptation and an intuitive storage level by using electrochromic materials polyaniline and zinc foil as the cathode and anode, and a ZnCl2 salt-encapsulated hydrogel as the electrolyte. The ECESD has good energy storage performance with an initial open-circuit voltage of about 1.43 V and an areal capacitance of up to 29.1 mF cm −2 (at 0.1 mA cm −2 ). Impressively, the ECESD has a fast self-charging ability. A fully drained ECESD can recharge to 82% of its original capacity in 10 minutes in air and is faster than most similar electrochromic devices. More importantly, the areal capacitance of the ECESD increased as the temperature was increased, suggesting that the ECESD possesses excellent adaptability to temperature. Moreover, the ECESD exhibited excellent capacity retention and cycling ability when operated at gradually changing temperatures (−25 °C to 50 °C). We envision that our research provides a new approach to the development of energy storage devices suitable for both cold and high temperatures in remote areas. This work provides a green, convenient, environmentally friendly, and cost-free fast charging strategy for electrochromic energy and combines a variety of smart features efficiently to promote the development of smart energy storage devices.